Pengaruh Film Rudy Habibie Terhadap Nasionalisme Siswa - Nanda Putri (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2020)
This study aims to determine what attracts students in watching Rudy Habibie films and the influence of watching Rudy Habibie films on student nationalism. To achieve this goal, the researcher used descriptive quantitative research method by distributing questionnaires directly to the students of SMA Unggul Ali Hasjmy, a number of samples that have been determined with certain conditions. The data collection technique used was through initial observation, questionnaires and documentation. Furthermore, the data processing technique was carried out using the help of the SPSS version 17 application to test the validity and reliability of the questionnaire, simple linear regression test, t test, and test the coefficient of determination. The results showed that the things that were of interest to the students were, among others, the content of the film, such as the story that was very inspiring, a figure who was described as having a high enthusiasm for learning and a love for the country, then in terms of the artistic side of the film, the character told even the shooting location. Then it was also found that there was an influence between watching Rudy Habibie films on student nationalism as evidenced by statistical calculations, the significant value was 0.000 or less than 0.05, which means that there was an influence and Ho was rejected and Ha was accepted. Then the t test shows the value of t count> t table or 6.287> 1.666 which means that there is a significant effect, then from the test results the coefficient of determination shows that the influence of variable X on variable Y is 34.9%.